Bars, Fast Food and Diners: Names and Functions of Refreshment Stands in the Cities of the Roman Empire (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The cities of Pompeii, Herculaneum and Ostia are a very remarkable source of data about the daily and commercial life of some shops, which had not only the possibility to sell food and drinks and to give the customers some rooms to have lunch, but also to accommodate with vehicles and animals: this work is the attempt to match the archaeological evidences with the definitions we have by ancient literature and, at the same time, to create a typological classification of these places by their dimensions, furniture and position in the urban contest.
Keywords: Pompeii; Herculaneum; Ostia; tabernae; shops; trade